Role of IPPs in energy sector of Pakistan, comparison with different countries and policies to ensure positive role - Muhammad Ali Afzal (NUST-2012-60724-MCES-64112-F); Dr Muhammad Bilal Khan (USPCAS-E, NUST, Islamabad, 2015)
TH-26
Keywords: MS-ESE Thesis MS Thesis